2017
DOI: 10.1186/s12906-017-2059-7
|View full text |Cite|
|
Sign up to set email alerts
|

Phoyunnanin E inhibits migration of non-small cell lung cancer cells via suppression of epithelial-to-mesenchymal transition and integrin αv and integrin β3

Abstract: BackgroundThe conversion of the epithelial phenotype of cancer cells into cells with a mesenchymal phenotype-so-called epithelial–mesenchymal transition (EMT)-has been shown to enhance the capacity of the cells to disseminate throughout the body. EMT is therefore becoming a potential target for anti-cancer drug discovery. Here, we showed that phoyunnanin E, a compound isolated from Dendrobium venustum, possesses anti-migration activity and addressed its mechanism of action.MethodsThe cytotoxic and proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 69 publications
4
25
0
Order By: Relevance
“…Recent publications suggest that Phoyunnanin E decreased the E-cadherin to N-cadherin switch and reduced upregulation of mesenchymal markers such as vimentin and snail, as well as slug expression. Phoyunnanin-E has also been shown to inhibit migration and growth and promote EMT suppression, reduce migratory-associated integrins αv and β3, and suppress FAK/AKT cascade, which subsequently suppressed downstream migratory proteins in lung cancer cells (Petpiroon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications suggest that Phoyunnanin E decreased the E-cadherin to N-cadherin switch and reduced upregulation of mesenchymal markers such as vimentin and snail, as well as slug expression. Phoyunnanin-E has also been shown to inhibit migration and growth and promote EMT suppression, reduce migratory-associated integrins αv and β3, and suppress FAK/AKT cascade, which subsequently suppressed downstream migratory proteins in lung cancer cells (Petpiroon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we further evaluated the downstream effectors of integrin including focal adhesion kinase (FAK), AKT, and p-AKT and small Rho GTPases family. There are many reports indicating that integrins initiate transmembrane signaling through activation of FAK and activate the downstream effectors such as AKT and Rho GTPases families for cancer cell migration [ 8 , 17 19 ]. Rho GTPases family including Ras, RhoA, Rac1, and Cdc42 are well known to regulate cytoskeleton remodeling, cell migration, malignant transformation, cell polarity, invasion, and metastasis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rho GTPases family including Ras, RhoA, Rac1, and Cdc42 are well known to regulate cytoskeleton remodeling, cell migration, malignant transformation, cell polarity, invasion, and metastasis [ 20 ]. Ras and Rac-1 regulate lamellipodia formation, Cdc42 stimulates plasma membrane protrusion filopodia, and RhoA promotes stress fiber formation [ 19 , 55 , 62 , 63 ]. Western blot analysis showed that rhodomyrtone significantly suppressed FAK expression and the downstream effectors including total AKT, phosphorylated AKT, Ras, RhoA, Rac1, and Cdc42 in SW1353 cell (Figures 6(c) and 6(f) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, gigantol, a bibenzyl compound extracted from Dendrobium draconis , has been shown to suppress EMT in non-small cell lung cancer H460 cells [ 22 ]. Petpiroon et al reported that phoyunnanin E inhibited the motility of lung cancer cells via the suppression of EMT and cancer metastasis-related integrins, such as integrin αv and integrin β3 [ 23 ]. Our previous results showed that ephemeranthol A, a natural compound isolated from D. infundibulum , also exhibited inhibitory effects on migration and EMT via suppression of the FAK-AKT signaling pathway [ 24 ].…”
Section: Discussionmentioning
confidence: 99%